EFL STUDENTS’ PERCEPTIONS TOWARDS YOUTUBE AS A MEDIUM FOR LEARNING ENGLISH IN JUNIOR HIGH SCHOOL - Tasya Reyna Shalsabilla; Ririn Pusparini (PROJECT (Professional Journal of English Education), 2022)
Currently, the development of modern technology in Indonesia is getting better, especially in terms of education which makes learning media very varied. One of them is YouTube as a learning medium has become a more popular medium for students. This study explores students' perceptions of using YouTube as a medium for learning English in Junior High School. This research is limited to 4 aspects of students' perceptions; Effectiveness, Attractiveness, Motivation, and Relevance. This study uses a qualitative method, with questionnaires and interviews as a research instrument. This research was carried out at one of the State Junior High Schools in Sidoarjo, which implemented YouTube as a medium for learning English. Data analysis used descriptive analysis. The results showed that many students agreed that YouTube is an effective learning medium. Moreover, it is not only effective, YouTube is attractive that can motivate students to learn because it contains words, pictures, and videos, but also an appropriate medium to deliver the learning materials. It can help students improve their English skills. However, some students seem to object to using YouTube as a learning medium since it takes up a lot of internet quota and makes them not focus on studying. Keywords:  Students’ Perception, Youtube Learning Media, Junior High School Students